(untitled) (Construction Economics and Building, 2024)
The utilization of Public Private Partnerships (PPPs) has become widely prevalent as an innovative approach for procuring public infrastructure projects. Risk transfer/allocation is one of the main reasons for this widespread adoption and considered a critical success factor for a PPP. Given the importance of equitable risk allocation, this study identified and analysed 10 key risk allocation criteria. Experts with experience in PPP projects in New Zealand were surveyed through an empirical questionnaire to obtain industry-wide data. Mean score analysis and factor analysis were then used to analyse the collected data. In order to ensure the validity of the analysis results, appropriate statistical tests such as Cronbach’s Alpha, Kaiser-Meyer-Olkin (KMO) statistic and Bartlett’s test of Sphericity were conducted. Result indicate that the most important criteria for risk allocation are “risk foresight”, “minimize risk loss” and “response to risk”. Furthermore, factor analysis showed that the identified RAC can be classified into three component groups namely “risk management expertise”, “core risk management capability” and “risk management strategy”. This study aims to provide PPP stakeholders with useful insights into the most effective measures for achieving equitable risk allocation. To achieve this, the study recommends to consider the risk management capabilities of both the public and private sectors in light of the identified RACs/groupings. The results of the study are expected to assist PPP stakeholders in developing strategies that can enhance risk management and achieve a fair distribution of risks.